PENERAPAN TANGGUNG JAWAB MUTLAK RUMAH SAKIT DALAM PELAYANAN KESEHATAN DI INDONESIA - Muhammad Ainurrasyid Al Fikri; Fatma Ulfatun Najicha (Universitas Negeri Semarang, 2022)
Doctor and patient are a legal relationship in a business engagement (inspanning verbintenis) and not a result bond (resultaat verbintenis). Even so, doctors are still responsible for any negligence that brings harm to patients. Until now, there is still confusion in Indonesia, whether medical liability is based on default or unlawful acts, even though as an inspiring verbintenis the basis for a suit that is more appropriate to use is an act against the law. This research was conducted by comparing the law with the statute approach, the conceptual approach and the case approach. Analysis of absolute responsibility cases in Indonesia is very necessary in order to provide justice for the community, especially in health law.